Influencia de la implementación del acuerdo de promoción comercial con Estados Unidos en los factores de comercialización en el sector farmacéutico peruano - Corti Ñavincopa, Rina (2021)
The Perú – United States Trade Promotion Agreement has brought multiple economic benefits after establishing relations with one of the most powerful countries worldwide. However, due to USA’s characteristic of being such developed country, their objectives defer from the objectives of a country that is still in development, like Perú, especially in matter of Intellectual Property. This can be confirmed considering that the United States is a big technology and investigation driver. Therefore, they look to protect their pharmaceutical industry so that high costs of innovation can be yielded due to the advantage of being the only actor in the market. In other words, a monopoly. The theory states that a developed country needs the competition to intensify so that prices can decrease and consequently the population can have appropriate access to medicines and a proper health system. Nevertheless, the agreements reached in negotiation rounds imply that the American inventions must be protected during a larger span of time than the accorded in multilateral organisms. This situation would lead to the laboratories enjoying a monopoly bigger that it already is and make price the main negative factor in the access of medicines. The objective of the investigation is to determine the impact of the Peru – United States Trade Promotion Agreement in terms of patents for commercial factors in the Peruvian pharmaceutical sector. For its achievement, through reliable sources, it was collected the necessary information for the analysis of the variable proposed within the years under study. The results obtained showed the respective trends for FDI, imports and prices fluctuation whether increasing or decreasing; as well as the negative or positive impact that other countries had in negotiations with United States regarding patents. In short, even though the agreement reached with the United States, in general terms, has meant benefits for Peru due to the tariff reductions, this hasn’t necessarily been reflected in the Intellectual Property chapter because the projected effects referred to medicines have not been fully complied. Even so, it is worth noting that the national pharmaceutical industry has not been affected in great magnitude.